The effect of various dilute administration of rocuronium bromide on both vascular pain and pharmacologic onset: a randomized controlled trial - Mayuko Kanazawa; Aiji Sato (Boku); Yoko Okumura; Mayumi Hashimoto; Naoko Tachi; Yushi Adachi; Masahiro Okuda (BMC Anesthesiology, 2019)
Abstract Background Rocuronium bromide (RB) is known to cause vascular pain. Although there have been a few reports that diluted administration causes less vascular pain, there have been no studies investigating diluted administration and the onset time of muscle relaxation. Therefore, we examined the influence of diluted administration of RB on the onset time of muscle relaxation and vascular pain. Methods 39 patients were randomly assigned to three groups: RB stock solution 10 mg/ml (Group 1), two-fold dilution 5 mg/ml (Group 2), or three-fold dilution 3.3 mg/ml (Group 3). After the largest vein of the forearm was secured, anesthesia was induced by propofol and 0.6 mg/kg of RB was administered. The evaluation method devised by Shevchenko et al. was used to evaluate the degree of vascular pain. The time from RB administration until the maximum blocking of T1 by TOF stimulation was measured. Results There was no significant difference in escape behaviors of vascular pain among the three groups, and the onset time of muscle relaxation was significantly slower in Group 3 than in Group 1 (p = 0.033). Conclusion Our results suggested that it is unnecessary to dilute RB before administration if a large vein in the forearm is used. Trial registration UMINCTR Registration number UMIN000026737. Registered 29 Mar 2017.